Towards a New Hierarchy of “Signs and Symptoms” - Bjørndal, Andreas N. (Homœopathic Links, 2012)
Symptoms are the building blocks in homeopathy. Hahnemann introduced the term signs and symptoms, where a sign is the objective manifestation and the symptom the subjective. The development of modern medicine, suggests signs should include medical findings. Hahnemann, suggested the division of the symptoms as in § 153 of his “Organon”. Here a new translation is suggested as Striking, Exceptional, Unusual and Distinctive (characteristic) signs and symptoms. The division of Kent, Vithoulkas and Hahnemann in § 9 are compared to modern and postmodern models of the structure, function, states, modes and development of the human consciousness. This promises possible enrichment of the homeopathic knowledge base in the process of perceiving and individualizing a case.
Keywords: Sign; Symptom; Medical findings; Emotional; Mental; Inbegriff; Genius; Local; Modality; Sensation; Essence; Unified concept; Unified abstraction; Kingdom; “Organon”